Diseño e implementación de un torno didáctico para elevar el nivel de enseñanza – práctica en el laboratorio de máquinas herramientas de la Universidad Técnica de Cotopaxi extensión la maná, año 2015 - Jácome Lozada, Cristhian René (2015)
This thesis arises from the need of students, teachers of the Technical University Extension Cotopaxi La Maná to implement a lathe as a machine - a teaching tool for students to achieve a practical learning. At present machining processes have had breakthrough with the development of technology, this is due to the research of new materials for cutting tools, which have better wear properties, increased cut resistance, high hardness, and there are innovations in alloys and coated materials.